Function Word Meaning, Uses, and Significance in Persian: Conjunctions as an Example - Hussen, Mahdi Ahmed (Al-Adab Journal, 2020)
Often Persian sentences do not end with a full stop. Rather, it is linked with other sentences with a word or a letter. In other words, it can be said that after completing the complete sentence and completing the meanings of the basic and subsequent sentences, the Persian sentence may be linked to the following sentence using one of the conjunctions. Conjunctions have a significant impact on the Persian language in terms of showing the meaning of the sentence, and interpreting the text; scientific research that has been written in this field has gained great importance.From here, the researcher has been working to sharpen his interest and make every effort to clarify what these conjuntions are, and use them in the Persian language; Based on what is stated in the Persian grammar books, and other relevant sources on this topic. The research included two main sections; the first: an overview of the types of articles, their definition, and an indication of their importance in the Persian language. As for the second, it was about conjunctions, and explaining their meanings and uses in the Persian language.Among the results of the research, the articles in Persian are divided into four groups; the first: letters of significance, second: letters of addition, and the third: sounds, and the fourth: conjunctions.There is no doubt that many definitions have been written to indicate the nature and uses of conjunctions; Among them: is a word used to connect two words, or two sentences, or two phrases with each other, and to indicate the type of relationship between them; Whether it is a conditional, temporal, or opposite relationship. Conjunctions in Persian are divided according to their meaning and uses over several groups. They are: temporal linking, passive linking, reciprocal linkage, causal linkage, target linkage, incremental linkage, conditional linking, crossover linking, and exceptional linking.